High-efficiency power generation system with integrated supercritical water gasification of coal. (15th September 2018) - Chen, Zhewen; Gao, Lin; Zhang, Xiaosong; Han, Wei; Li, Sheng
Abstract: A novel power generation system with integrated supercritical water gasification (SCWG) of coal is proposed in this article. The gasification product directly enters the supercritical turbine to generate electricity. After pressure relief, the syngas separated from the unreacted water is transferred to the combined cycle. The influences of coal-water-slurry concentration (CWSC) and the outlet pressure ( P h ) of the supercritical turbine on the system performances are studied. The results show that the thermal efficiency increases with increasing CWSC or decreasing P h . The ultimate thermal efficiency of the system can be obtained when the CWSC is 25 wt% and P h is 1 bar, which can approach 54.68%. The thermal efficiency of the novel system is higher than that of the power generation system with integrated SCWG of coal and parallel chemical heat recovery. Highlights: A novel power generation system with supercritical water gasification of coal is proposed. The energy balance of the system is conducted. A maximum thermal efficiency of 54.38% is obtained.